Connaissance de la connaissance et connaissance par corps en STAPS - Vanpoulle, Y. (Movement & Sport Sciences - Science & Motricité, 2016)
Is it possible to define a knowledge of the embodied knowledge that the Exercise and Sport Science (STAPS), through its topic the motor action, could enable to emerge? Regarding the central position of praxis as an activity indirectly reachable, underlying théôria and techné, and a body, object and subject, producer and product of this praxis, STAPS is legitimate to be part of the main paradigm renewal, that is currently happening in science, but also in the whole world. It is possible, by crossing the newest evolutions of science with more traditional forms of knowledge, to define three modes of phenomenological knowledge that build knowledge as well as body, situation as well as global world. The phenomenological choice and these three modes of knowledge - in positivist exteriority, in comprehensive dynamic exteriority-interiority, in interiority of the body and the situation-world - could be the opportunity to develop a specific way of knowing in STAPS, but also through the STAPS, for a renewal of epistemology and of our relationships to the world.